Laryngospasm during general anaesthesia in the cat : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University - Rex, Michael Albert Edward (Massey University, 1969)
One of the many hazards of general anaesthesia is spasm of the muscles of the air passages - that is laryngospasm, tracheal spasm and bronchospasm. When any one of these is severe, it can lead to hypoxia or anoxia and death, in addition to less serious sequelae such as the formation of ulcers and granulomata in the larynx and trachea. This thesis is concerned with one of these conditions - laryngospasm, which nay be defined as an occlusion of the aditus laryngis by the action of the intrinsic laryngeal muscles. The investigation has been in the nature of en experimental study on the induction of and the mechanisms involved in laryngospasm. A clearer definition of these mechanism is essential if the occurrence of this condition during anaesthesia is to be prevented. In particular, attempts have been made to define both the sites of stimulation, and the afferent and efferent limbs of the laryngeal reflex responses stimulated by the inhalation of anaesthetic vapours. The work is an extension as well as a confirmation of preliminary communications (Rex, 1966, 1967), reprints of which are provided as appendices 1 and 2. Interest in this study arose from clinical experience and an awareness of the problem laryngospasm presents in anaesthesia.
Keywords: Laryngospasm; Laryngeal muscles; Anaesthesia; Cat surgery